Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
The average rate of change of g from x = a to x = a + h is -3.
Step-by-step explanation:
We are given the function:
[tex]g(x) = -3x + 4[/tex]
And we want to determine its average rate of change of the function for x = a and x = a + h.
To determine the average rate of change, we find the slope of the function between the two points. In other words:
[tex]\displaystyle \text{Avg} = \frac{g(a + h) - g(a) }{(a + h ) - a}[/tex]
Simplify:
[tex]\displaystyle \begin{aligned} \text{Avg} &= \frac{g(a + h) - g(a) }{(a + h ) - a} \\ \\ &=\frac{(-3(a+h) + 4) - (-3a+4)}{h} \\ \\ &= \frac{(-3a -3h + 4) + (3a - 4) }{h} \\ \\ &= \frac{-3h}{h} \\ \\ &= -3\end{aligned}[/tex]
In conclusion, the average rate of change of g from x = a to x = a + h is -3.
This is the expected result, as function g is linear, so its rate of change would be constant.
We hope this was helpful. Please come back whenever you need more information or answers to your queries. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.